Fossil vertebrate studies in Rhodesia: sphenodontid remains from the upper Trias of Rhodesia - Gow, C. E. (Bernard Price Institute for Palaeontological Research, 1977)
Small sphenodontid rhynchocephalians are known from the upper Trias in Britain (Robinson, 1973). This paper records for the first time the presence of sphenodontids of very similar age, size, and morphology from the Upper Trias of Rhodesia.
None
Keywords: sphenodontids; Triassic; Rhodesia